Antenatal corticosteroids for management of preterm birth: a multi-country analysis of health system bottlenecks and potential solutions. (December 2015) - Liu, Grace; Segrè, Joel; Gülmezoglu, A; Mathai, Matthews; Smith, Jeffrey; Hermida, Jorge; Simen-Kapeu, Aline; Barker, Pierre; Jere, Mercy; Moses, Edward; Moxon, Sarah; Dickson, Kim; et al.
Abstract Background Preterm birth complications are the leading cause of deaths for children under five years. Antenatal corticosteroids (ACS) are effective at reducing mortality and serious morbidity amongst infants born at <34 weeks gestation. WHO guidelines strongly recommend use of ACS for women at risk of imminent preterm birth where gestational age, imminent preterm birth, and risk of maternal infection can be assessed, and appropriate maternal/newborn care provided. However, coverage remains low in high-burden countries for reasons not previously systematically investigated. Methods The bottleneck analysis tool was applied in 12 countries in Africa and Asia as part of theEvery Newborn Action Plan process. Country workshops involved technical experts to complete the survey tool, which is designed to synthesise and grade health system "bottlenecks", factors that hinder the scale up, of maternal-newborn intervention packages. We used quantitative and qualitative methods to analyse the bottleneck data, combined with literature review, to present priority bottlenecks and actions relevant to different health system building blocks for ACS. Results Eleven out of twelve countries provided data in response to the ACS questionnaire. Health system building blocks most frequently reported as having significant or very major bottlenecks were health information systems (11 countries), essential medical products and technologies (9 out of 11 countries) and health service delivery (9 out of 11 countries). Bottlenecks included absence of coverage data, poor gestational age metrics, lack of national essential medicines listing, discrepancies between prescribing authority and provider cadres managing care, delays due to referral, and lack of supervision, mentoring and quality improvement systems. Conclusions Analysis centred on health system building blocks in which 9 or more countries (>75%) reported very major or significant bottlenecks. Health information systems should include improved gestational age assessment and track ACS coverage, use and outcomes. Better health service delivery requires clarified policy assigning roles by level of care and cadre of provider, dependent on capability to assess gestational age and risk of preterm birth, and the implementation of guidelines with adequate supervision, mentoring and quality improvement systems, including audit and feedback. National essential medicines lists should include dexamethasone for antenatal use, and dexamethasone should be integrated into supply logistics.